Biohydrogen Production from Palm Oil Mill Effluent Using Immobilized Clostridium Butyricum EB6 in Polyethylene Glycol - Singh, Lakhveer; Zularisam, A. W.; Siddique, Md. Nurul Islam; Anwar, Ahmad; Mohd Hasbi, Ab. Rahim; Mimi Sakinah, A. M. (Elsevier Ltd, 2013)
A novel polyethylene glycol (PEG) gel was fabricated and used as a carrier to immobilize Clostridium butyricum EB6 to improve biohydrogen (bio-H2) production from palm oil mill effluent (POME). POME is used as a substrate that can act as a carbon source. The resulting PEG-immobilized cells were found to yield 5.35 LH2/L-POME, and the maximum H2 production rate was 510 mL H2/L-POME h (22.7 mmol/L h). The Monod-type kinetic model was used to describe the effect of substrate (POME) concentration on the H2 production rate. The acclimation of immobilized cells greatly improved H2 production. Batch experiments demonstrated that particle size of PEG-immobilized cells for efficient H2 production 3 mm. It is significant that this is the first report on whole-cell immobilization in PEG for H2 production from POME.